Faktor-Faktor Yang Memengaruhi Customer Loyalty Melalui Customer Satisfaction Pada Pengguna Kartu Kredit Bank Mandiri di Bekasi - Natasya, Desita Aulia; Marie, Andhalia Liza (Program Pascasarjana STIE Amkop Makassar, 2024)
The purpose of this study was to determine the factors that influence the customer loyalty through customer satisfaction for Bank Mandiri redit card users in Bekasi. The data used in this study are based on primary data in the form of questionnaires distributed to respondents. Sampling was carried out using Non-probability Sampling technique, namely Purposive Sampling of 105 respondents. The research object used in this research is Bank Mandiri Credit Card users. The analysis method used in this research is SmartPLS. The results of this study indicate that there is an effect of service experience on customer loyalty through customer satisfaction, trust affects customer loyalty through customer satisfaction, and service experience, trust, customer satisfaction affect customer loyalty.